The development of a recovery coaching training curriculum to facilitate linkage to and increase retention on medications for opioid use disorder - Moffitt, Trevor; Fallin-Bennett, Amanda; Fanucchi, Laura; Walsh, Sharon L.; Cook, Christopher; Oller, Devin; Ross, Anna; Gallivan, Molly; Lauckner, John; Byard, Jeremy; Wheeler-Crum, Phoebe; Lofwall, Michelle R. (Frontiers in Public Health, 2024)
Introduction Medication treatment for opioid use disorder (MOUD) decreases opioid overdose risk and is the standard of care for persons with opioid use disorder (OUD). Recovery coach (RC)-led programs and associated training curriculums to improve outcomes around MOUD are limited. We describe our comprehensive training curriculum including instruction and pedagogy for novel RC-led MOUD linkage and retention programs and report on its feasibility. Methods–pedagogy and training development The Kentucky HEALing (Helping to End Addiction Long-termSM) Communities Study (HCS) created the Linkage and Retention RC Programs with a local recovery community organization, Voices of Hope-Lexington. RCs worked to reduce participant barriers to entering or continuing MOUD, destigmatize and educate on MOUD and harm reduction (e.g., safe injection practices), increase recovery capital, and provide opioid overdose education with naloxone distribution (OEND). An extensive hybrid (in-person and online, both synchronous and asynchronous), inclusive learning-focused curriculum to support the programs (e.g., motivational interviewing sessions, role plays, MOUD competency assessment, etc.,) was created to ensure RCs developed the necessary skills and could demonstrate competency before deployment in the field. The curriculum, pedagogy, learning environment, and numbers of RCs trained and community venues receiving a trained RC are reported, along with interviews from three RCs about the training program experience. Results The curriculum provides approximately 150 h of training to RCs. From December 2020 to February 2023, 93 RCs and 16 supervisors completed the training program; two were unable to pass a final competency check. RCs were deployed at 45 agencies in eight Kentucky HCS counties. Most agencies (72%) sustained RC services after the study period ended through other funding sources. RCs interviewed reported that the training helped them better explain and dispel myths around MOUD. Conclusion Our novel training and MOUD programs met a current unmet need for the RC workforce and for community agencies. We were able to train and deploy RCs successfully in these new programs aimed at saving lives through improving MOUD linkage and retention. This paper addresses a need to enhance the training requirements around MOUD for peer support specialists.